Evaluation of the Efficacy and Safety of a Compound of Micronized Flavonoids in Combination With Vitamin C and Extracts of Centella asiatica, Vaccinium myrtillus, and Vitis vinifera for the Reduction of Hemorrhoidal Symptoms in Patients With Grade II and III Hemorrhoidal Disease: A Retrospective Real-Life Study - Gravina, Antonietta G.; Pellegrino, Raffaele; Facchiano, Angela; Palladino, Giovanna; Loguercio, Carmelina; Federico, Alessandro (Frontiers in Pharmacology, 2021)
Background and aim: Several evidences have shown how, in hemorrhoidal disease, phlebotonic flavonoid agents as quercetin reduce capillary permeability by increasing vascular walls resistance and how rutin and vitamin C have antioxidant properties and Centella asiatica has reparative properties towards the connective tissue. A retrospective study was designed in order to evaluate the efficacy and safety of a compound consisting of micronized flavonoids in combination with vitamin C and extracts of Centella asiatica, Vaccinium myrtillus and Vitis vinifera for grade II and III hemorrhoidal disease. Patients and methods: Data of 49 patients, over 18, who were following a free diet regimen, not on therapy with other anti-hemorrhoid agents, treated with a compound consisting of 450 mg of micronized diosmin, 300 mg of Centella asiatica, 270 mg of micronized hesperidin, 200 mg of Vitis vinifera, 160 mg of vitamin C, 160 mg of Vaccinium myrtillus, 140 mg micronized quercetin and 130 mg of micronized rutin (1 sachet or 2 tablets a day) for seven days were collected. Hemorrhoid grade according to Goligher’s scale together with anorectal symptoms (edema, prolapse, itching, thrombosis, burning, pain, tenesmus, bleeding) both before treatment (T0) and after seven days of therapy (T7) were collected. Primary outcomes were the reduction of at least one degree of hemorrhoids according to the Goligher’s scale assessed by proctological examination and compound safety. Secondary outcome was the reduction of anorectal symptoms assessed by questionnaires administered to patients. Results: Forty-four patients (89.8%) presented a reduction in hemorrhoidal grade of at least one grade (p < 0.001). No adverse events with the use of the compound were noted. Significant reduction was observed in all anorectal symptoms evaluated (p < 0.05). No predictors of response to the compound were identified among the clinical and demographic variables collected. Conclusion: The compound analyzed was effective and safe for patients with grade II and III hemorrhoidal disease according to Goligher’s scale.